Modulation of osteogenic differentiation in human skeletal cells in Vitro by 5-azacytidine. - Locklin, R; Oreffo, R; Triffitt, J (1998)
Cellular differentiation is controlled by a variety of factors including gene methylation, which represses particular genes as cell fate is determined. The incorporation of 5-azacytidine (5azaC) into DNA in vitro prevents methylation and thus can alter cellular differentiation pathways. Human bone marrow fibroblasts and MG63 cells treated with 5azaC were used as models of osteogenic progenitors and of a more mature osteoblast phenotype, respectively. The capacity for differentiation of these cells following treatment with glucocorticoids was investigated. 5azaC treatment led to significant expression of the osteoblastic marker alkaline phosphatase in MG63 osteosarcoma cells, which was further augmented by glucocorticoids; however, in human marrow fibroblasts alkaline phosphatase activity was only observed in glucocorticoid-treated cultures. MG63 cells represent a phenotype late in the osteogenic lineage in which demethylation is sufficient to induce alkaline phosphatase activity. Marrow fibroblasts are at an earlier stage of differentiation and require stimulation with glucocorticoids. In contrast, the expression of osteocalcin, an osteoblastic marker, was unaffected by 5azaC treatment, suggesting that regulation of expression of the osteocalcin gene does not involve methylation. These models provide novel approaches to the study of the control of differentiation in the marrow fibroblastic system.